2019
DOI: 10.3762/bjoc.15.200
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1-azaspiro[4.4]nonan-1-oxyls via intramolecular 1,3-dipolar cycloaddition

Abstract: Sterically shielded nitroxides of the pyrrolidine series have shown the highest resistance to reduction. Here we report the synthesis of new pyrrolidine nitroxides from 5,5-dialkyl-1-pyrroline N-oxides via the introduction of a pent-4-enyl group to the nitrone carbon followed by an intramolecular 1,3-dipolar cycloaddition reaction and isoxazolidine ring opening. The kinetics of reduction of the new nitroxides with ascorbate were studied and compared to those of previously published (1S,2R,3′S,4′S,5′S,2″R)-disp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…To avoid overoxidation to oxoammonium cations with possible affection of the hydroxymethyl groups (cf. [42,43]), the amines were treated with ca. one equivalent of the oxidant.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid overoxidation to oxoammonium cations with possible affection of the hydroxymethyl groups (cf. [42,43]), the amines were treated with ca. one equivalent of the oxidant.…”
Section: Resultsmentioning
confidence: 99%
“…1,3-dipolar cycloaddition, isoxazolidine ring opening and oxidation [27,30]. The literature protocol implies multi-step synthesis with low overall yield (ca.…”
Section: Synthesismentioning
confidence: 99%
“…This parameter is very important for distance measurement using Saturation Recovery (SR) method, another pulsed EPR technique widely used in structural biology [2,21]. The nitroxide 1 was prepared from 3,4-di-tert-butoxypyrroline 1-oxide [31] via repetitive sequence of procedures: pent-4-en-1-ylmagnesium bromide addition, intramolecular The nitroxide 1 was prepared from 3,4-di-tert-butoxypyrroline 1-oxide [31] via repetitive sequence of procedures: pent-4-en-1-ylmagnesium bromide addition, intramolecular 1,3dipolar cycloaddition, isoxazolidine ring opening and oxidation [27,30]. The literature protocol implies multi-step synthesis with low overall yield (ca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, the same researchers suggested that the presence of electron-withdrawing tert -butoxy groups at positions 3 and 4 of the pyrrolidine ring of 221 can strongly affect the rate of nitroxide reduction; therefore, the removal of these groups should cause a further decrease in the reduction rate of the corresponding nitroxide. In this regard, they developed a method for the synthesis of SNRs of C 1 -symmetric racemic 3,4-unsubstituted pyrrolidine nitroxides 236a–c with only one spiro (2-hydroxymethyl) cyclopentane moiety ( Scheme 41 ) [ 151 ]. Before the step of oxidation of the secondary amino group to a radical in this sequence, acyl protection of the primary alcohol group ( 237 → 238 ) is carried out.…”
Section: 25-dihydropyrrole (3-pyrroline)- and Pyrrolidine (Proxylmentioning
confidence: 99%